Guidelines on How to implement MaaS in Local Contexts - Stella Aaltonen; Milla Wiren; Aki Koponen; Helber Y. López Covaleda; Nuppu Ervasti; Nuria Blanco; Christian Grundmann; Helene Carlsson; Nikolay Simeonov; Ruth Schawohl (Civitas Initiative, 2022)
"Guidelines on how to implement MaaS in local contexts" – summarizes the lessons learnt in the CIVITAS ECCENTRIC project during the years 2016–2020. The project was the first to include measures focusing on the concept Mobility as a Service, (MaaS), which in 2016 was still brand new in the world of mobility planning. In the report, you will find the updated version of the readiness level indicators. These indicators have been updated based on several workshops carried out on them during the years 2018‒2020.
The report focuses on five different areas related to MaaS :
• Chapter 2 on context outlines the principles and circumstances necessary for MaaS to flourish.
• Chapter 3 on key pillars focuses on business models and stakeholder involvement.
• Chapter 4 on user-centric approach highlights the main points to take into consideration when designing services.
• Chapter 5 on MaaS readiness levels introduces the updated readiness level indicators.
• Chapter 6 on MaaS readiness levels in ECCENTRIC cities highlights achievements in each city.